The Role of School Administration in Developing Creativity and Its Obstacles as Perceived by School Principals in Government Schools in the Directorate of University District - Bdair, Sana Said (Journal of Educational and Psychological Sciences, 2021)
This study aims at identifying the role of school administration in developing creativity and its obstacles as perceived by school principals in government schools in the directorate of University District. This may be attributed to variables of gender, academic qualification, years of experience, and school level. The researcher has used the descriptive analytical method through employing the use of a questionnaire. This questionnaire has been made of 36 sections. 28 sections were designed to identify the role of school administration in developing creativity in the government schools in the directorate of the university district, and 8 to identify the obstacles that face the school’s administration. A sample of 55 male and female principals in government schools in the directorate of the university district have been chosen for the academic year 2019/2020. The results of the study showed that the application of creativity by the school principals in government schools have an overall average of (3.5 out of 5), which is rated as high. For the other two main areas, the administration one resulted with an average of (4.03) with a high rate, and for the obstacles area it resulted with (3.68) and was rated as large obstacles. It also has shown that there were no statistically significant differences in the role of school administration in developing creativity in government schools, which might be attributed to variables of academic qualification, years of experience, and school’s level. However, there was a significant difference attributed to the gender variable, and it was in the favor of females. Based on those results, the researcher suggested a number of recommendations for developing creativity and limiting its obstacles at Jordanian Schools and other Arab countries.